A systematic review of instruments assessing dimensions of distress among caregivers of adult and pediatric cancer patients. Issue 1 (29th March 2016) - Tanco, Kimberson; Park, Ji Chan; Cerana, Agustina; Sisson, Amy; Sobti, Nikhil; Bruera, Eduardo
Abstract: Objective: Caregivers of cancer patients face intense demands throughout the course of the disease, survivorship, and bereavement. Caregiver burden, needs, satisfaction, quality of life, and other significant areas of caregiving are not monitored regularly in the clinic setting, resulting in a need to address the availability and clinical effectiveness of cancer caregiver distress tools. This review aimed to determine the availability of cancer caregiver instruments, the variation of instruments between different domains of distress, and that between adult and pediatric cancer patient populations. Method: A literature search was conducted using various databases from 1937 to 2013. Original articles on instruments were extracted separately if not included in the original literature search. The instruments were divided into different areas of caregiver distress and into adult versus pediatric populations. Psychometric data were also evaluated. Results: A total of 5, 541 articles were reviewed, and 135 articles (2.4%) were accepted based on our inclusion criteria. Some 59 instruments were identified, which fell into the following categories: burden ( n = 26, 44%); satisfaction with healthcare delivery ( n = 5, 8.5%); needs ( n = 14, 23.7%); quality of life ( n = 9, 15.3%); and other issues ( n = 5, 8.5%). The median number of items was 29 (4–125): 20/59 instruments (33.9%) had ≤20 items; 13 (22%) had ≤20 items and were psychometrically sound, with 12 of these 13 (92.3%) being self-report questionnaires. There were 44 instruments (74.6%) that measured caregiver distress for adult cancer patients and 15 (25.4%) for caregivers of pediatric patients. Significance of results: There is a significant number of cancer caregiver instruments that are self-reported, concise, and psychometrically sound, which makes them attractive for further research into their clinical use, outcomes, and effectiveness.